Step-by-step explanation:
an = 2n^2 - 3 · Anonymous. -1, 5, 15, 29, 47, ... an = 2 n^2 - 3.
- 4x + 16y + 24z
- = 4(x + 4y + 6z)
<u>Answer</u><u>:</u>
<u>4</u><u>(</u><u>x </u><u>+</u><u> </u><u>4</u><u>y</u><u> </u><u>+</u><u> </u><u>6</u><u>z</u><u>)</u>
Hope you could understand.
If you have any query, feel free to ask
A. we use the z statistic to solve this problem
z = (x – u) / s
We calculate the value of the sample mean u and standard deviation
s:
u = $30 * 304 = $9120
s = $21 * 304 = $6384
z = (9,600 – 9120) / 6384
z = 0.075
From the normal tables using right tailed test,
P = 0.47
B. At worst 11% means P = 0.11, so the z value at this is
z = -1.23
-1.23 = (x – 9120) / 6384
x = 1267.68
Answer:
Step-by-step explanation: candy
The correct answer is y-axis, x-axis, y-axis, x-axis.